Membangun Sistem Manajemen Supply Chain pada PT Arta Daya Taruna - Purnomo, Liu; Muchlis, M (STIKOM Tunas Bangsa Pematangsiantar, 2026)
This research aims to design and implement a web-based Supply Chain Management (SCM) system at PT Arta Daya Taruna to improve the efficiency of internal logistics management in the mining environment. The manual process that was previously used caused various problems such as procurement delays, duplicate requests, loss of physical documents, and low real-time visibility of stock. The research uses waterfall model software engineering methods which include the needs analysis stage, UML-based system design, implementation, testing, and maintenance. The system is developed using Next.js, TypeScript, MySQL, and Prisma technologies with the main features of Work Order (WO), Purchase Requisition (PR), Purchase Order (PO), Goods Receipt (GR), Material Requisition (MR), and Goods Issue (GI) in one integrated platform. The system is equipped with role-based access control, automatic notifications via email and WhatsApp, and real-time inventory monitoring dashboard. The results of the two-month trial showed a significant increase in operational efficiency, namely a reduction in WO to GI processing time from 10 days to less than 3 days, elimination of physical document loss, acceleration of stock report generation from two days to one hour, and an increase in inventory accuracy from 85% to 98%. The user satisfaction rate is also in the high category with an average score of 4.2 out of 5. This system has been proven to be able to improve transparency, accountability, and speed of decision-making in dynamic mine operations.